Who was Georgia O'Keeffe? - Fabiny, Sarah (Who is-- ?, 2022)
"Georgia O'Keeffe is famously known for her colorful, large paintings of flowers, but this artist's portfolio expands far beyond Jack-in-the-pulpits. In this book, young readers will learn about O'Keeffe's childhood in Wisconsin and her years as a talented art school teacher. Her years as an artist in both New York and New Mexico, two areas that are heavily represented in her artwork, reveal O'Keeffe's influences. Explore the adventures that inspired O'Keeffe's paintings of skyscrapers, barns, skulls, and flowers, and made her into an American art icon of the twentieth century"--